2014
DOI: 10.1371/journal.pone.0099333
|View full text |Cite
|
Sign up to set email alerts
|

Among-Population Variation in Tolerance to Larval Herbivory by Anthocharis cardamines in the Polyploid Herb Cardamine pratensis

Abstract: Plants have two principal defense mechanisms to decrease fitness losses to herbivory: tolerance, the ability to compensate fitness after damage, and resistance, the ability to avoid damage. Variation in intensity of herbivory among populations should result in variation in plant defense levels if tolerance and resistance are associated with costs. Yet little is known about how levels of tolerance are related to resistance and attack intensity in the field, and about the costs of tolerance. In this study, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 47 publications
(61 reference statements)
0
18
1
Order By: Relevance
“…Resistance was calculated by standardizing the time it took for a plant to receive an egg in a contextually controlled cage experiment by subtracting the mean oviposition time and dividing it by the standard deviation of the trial (for details see König et al. ). Negative values of resistance represent low resistance against oviposition and positive values represent high resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance was calculated by standardizing the time it took for a plant to receive an egg in a contextually controlled cage experiment by subtracting the mean oviposition time and dividing it by the standard deviation of the trial (for details see König et al. ). Negative values of resistance represent low resistance against oviposition and positive values represent high resistance.…”
Section: Resultsmentioning
confidence: 99%
“…; König et al. ). The ability to avoid oviposition by A. cardamines should thus be an important component of overall resistance to herbivory in C. pratensis in this region.…”
Section: Introductionmentioning
confidence: 96%
“…One factor that might have contributed to the observed differences among species in latitudinal patterns of phenology is differences in the intensity of herbivory. For our study species, larval feeding of the butterfly A. cardamines can severely influence plant fitness (Wiklund and Friberg , König et al ) and the risk of butterfly attack has been shown to be related to flowering phenology and to differ among the study species and among regions (Wiklund and Åhrberg , Navarro‐Cano et al ). However, it is also true that many other factors varying at smaller spatial scales may have influenced the observed differences among regions and that further studies are necessary to identify the important selective agents.…”
Section: Discussionmentioning
confidence: 98%
“…Both the abundance of the crucifer host species and attack rates on individual species have been shown to vary among study species (Wiklund and Åhrberg ), regions (Navarro‐Cano et al ) and years (Wiklund and Friberg ). Larvae consume the reproductive parts of the plant and sometimes also vegetative parts, resulting in markedly reduced plant fitness (Wiklund and Friberg , König et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Hosting a larva also leads to fitness losses the following flowering season; both tetraploids and octoploids produce fewer flowers and are less likely to flower the year after butterfly attack (König et al. ).…”
Section: Methodsmentioning
confidence: 99%